The cingulate oculomotor cortex. (May 2021) - Ruehl, Ria Maxine; Ophey, Leoni; Ertl, Matthias; zu Eulenburg, Peter
Abstract: Knowledge about the relevance and extent of human eye movement control in the cingulate cortex to date is very limited. Experiments in non-human primates brought about evidence for a potentially central role of the dorsal bank of the cingulate sulcus in saccadic eye movements. In humans, a putative cingulate eye field (CEF) in the same region has been proposed; however, its function and location still remain controversial. Another area in the posterior cingulate cortex, the cingulate sulcus visual area (CSv), has been shown to respond to visual motion cues and also ocular motor tasks. In this study we used multi-band neuroimaging (n = 46) to comprehensively characterize oculomotor responses along the entire cingulate cortex during the most common types of eye movements. We were able to robustly localize the CEF to the anterior portion of the midcingulate gyrus. The region gave responses during all oculomotor tasks and is embedded within the ventral attention network. Area CSv, which is located in the anterior portion of the posterior cingulate gyrus, on the other hand responded to smooth pursuit and optokinetic nystagmus only. It likewise represents a node within the ventral attention network but at the same time seems to be a distinctive part of the somatomotor network. Our findings support an executive role of the CEF, suggesting a cognitive control function in maintaining and adapting different kinds of eye movements. CSv on the other hand might be an interface for relaying oculomotor, visual motion and broad sensory signals related to self-motion.